a) (x-1) *(x+4)- (x+5) * x
b) (x-2) *(x-3)- (2x-1)*(x+1)
va rog ajutatima
Răspunsuri la întrebare
Răspuns de
1
A)(X-1)*(x+4)-(x+5)*x=x^2+4x-x-4-(x^2+5x)=x^2+3x-4-x^2-5x=-2x-4=-2 (x+2)
B)(x-2)(x-3)-(2x-1)(x+1)=x^2-3x-2x+6-(2x^2+2x-x-1)=x^2-5x+6-2x^2-x+1=-x^2-6x+7
Răspuns de
2
a) (x-1)(x+4)-x(x+5)=x²+4x-x-4-x²-5x=4x-x-5x=-2x-4
b) (x-2)(x-3)-(2x-1)(x+1)=x²-3x-2x+6-2x²-2x+x+1=-x²-6x+7
b) (x-2)(x-3)-(2x-1)(x+1)=x²-3x-2x+6-2x²-2x+x+1=-x²-6x+7
Alte întrebări interesante
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă